Development of bacterial cellulose–ZnO–MWCNT hybrid membranes: a study of structural and mechanical properties. Issue 6 (24th June 2020) - El Mrabate, Bilal; Udayakumar, Mahitha; Csiszár, Emília; Kristály, Ferenc; Leskó, Máté; Somlyai Sipos, László; Schabikowski, Mateusz; Németh, Zoltán
Abstract : Self-supported and flexible bacterial cellulose (BC) based hybrid membranes were synthesized and decorated with zinc oxide/multi-walled carbon nanotube (ZnO–MWCNT) composite additives in order to modify and tune their surface and bulk properties. Two types of ZnO–MWCNT additives with different morphologies were used in a wide concentration range from 0 to 90% for BC-based hybrids produced by filtration. The interaction between BC and ZnO–MWCNT and the effect of concentration and morphology of additives on the properties like zeta potential, hydrophilicity, electrical conductivity, etc. would be an important factor in various applications. Furthermore, the as-prepared hybrid membranes were characterized with the use of scanning electron microscopy (SEM), focused ion beam scanning electron microscopy (FIB-SEM), energy dispersive X-ray spectroscopy (EDS), X-ray powder diffraction (XRD) and surface area measurement (BET). Applying the presented synthesis routes, the surface properties of BC-based membranes can be tailored easily. Results reveal that the as-prepared BC–ZnO–MWCNT hybrid membranes can be ideal candidates for different kinds of applications, such as water filtration or catalysts.